C-H functionalization of imidazo[1,5-a]pyridines: a metal-free approach for methylene insertion to access C(sp2)-C(sp3)-H-C(sp2) bond formation - Mahajan, Shivangani; Sawant, Sanghapal D. (ACS Omega, 2024)
Formaldehyde has been used as a solvent and a source of carbon to insert a methylene group for bridging two imidazo[1,5-a]pyridine molecules without using any metal catalysis. This strategy has been extended on other alkyl-, aryl-, and heteroaryl aldehydes as well. This C(sp2)-C(sp3)-H-C(sp2) bond forming reaction proceeds via C(sp2)H functionalization of imidazo[1,5-a]pyridine and was applied on a wide range of substrates offering moderate to good yields of methylene-bridged/inserted bis-imidazo[1,5-a]pyridines. Most importantly, as an application, the bis-heteroarene product has been demonstrated as a ligand. The ligand-like behavior of bis-imidazo[1,5-a]pyridines has been demonstrated as an extension of current methodology. This reaction works well at the gram scale level.